2021
DOI: 10.3390/biom11081190
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Fe-EDTA and Sodium Silicate Affects the Polyphenols Content in Broccoli and Radish Sprouts

Abstract: The effects of elicitors on broccoli (Brassica oleracea L. var. Italica) and radish (Raphanus sativus L.) sprouts were evaluated. Seeds and then sprouts were soaked daily for 30 min over 6 days in water (control) or a mixture of FeEDTA and sodium silicate or sodium silicate alone. The contents of the flavonoids and phenolic acids (free, esters, and glycosides) were determined using HPLC-ESI-MS/MS. Phenolic compounds were released from the esters after acid hydrolysis and from the glycosides using alkaline hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
2
0
1
Order By: Relevance
“…However, the studied sprouts exhibited significantly different concentrations of total (poly)phenols, as follows: broccoli (137.88 mg/g fresh weight (fw)) > white mustard (120.95 mg/g fw) > red cabbage (108.03 ng/g fw) > red radish (64.25 mg/g fw) (Figure 2). These concentrations are in good agreement with previous descriptions in the literature [18][19][20]. However, in order to understand the biological interest of cruciferous sprouts' phenolics, the analysis of bioaccessibility needs to be addressed.…”
Section: Content Of Flavonols and Hydroxycinnamic Acids In The Raw Cruciferous Sproutssupporting
confidence: 88%
“…However, the studied sprouts exhibited significantly different concentrations of total (poly)phenols, as follows: broccoli (137.88 mg/g fresh weight (fw)) > white mustard (120.95 mg/g fw) > red cabbage (108.03 ng/g fw) > red radish (64.25 mg/g fw) (Figure 2). These concentrations are in good agreement with previous descriptions in the literature [18][19][20]. However, in order to understand the biological interest of cruciferous sprouts' phenolics, the analysis of bioaccessibility needs to be addressed.…”
Section: Content Of Flavonols and Hydroxycinnamic Acids In The Raw Cruciferous Sproutssupporting
confidence: 88%
“…Sodium silicate 1.0 mM, 2 h 60 • C in aerial showed the best results, whereas sodium silicate 1.0 mM 1 h 40 • C was the best for media treatment in sodium silicate-treated extracts with the content of 1183.52 ± 23.02 and 1017.42 ± 4.605 mg GAE/100 g, respectively. It was previously reported that the sodium silicate treatment enhances the total phenolic content when treated with Fe-EDTA and sodium [47,48]. Overall, phenolic content remained stable across different temperatures and time points.…”
Section: Impact On Total Phenolic and Flavonoid Contentmentioning
confidence: 52%
“…This bioprocess also enhances vitamin and bioactive compound levels. Common seeds used for sprouts include alfalfa (Logan et al, 2001 ; Zhang et al, 2022 ), broccoli (Chiriac et al, 2020 ; Subedi et al, 2019 ), clover (Dębski et al, 2021 ; Zhang et al, 2022 ), radishes (Subedi et al, 2019 ), rapeseed (Galanty et al, 2022 ), Chinese cabbage, red cabbage, barley, and wheat (Xiao et al, 2022 ). However, the contents may differ depending on the cultivation method of the plant (Galanty et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%